AFFORDANCES IN THE HOME ENVIRONMENT AND MOTOR DEVELOPMENT IN PRESCHOOL CHILDREN - Sales Nobre, Francisco Salviano (2012)
The aim of this research was to verify the correlation between the opportunities of motor stimulation in the home environment and the level of motor development (MD) in 12 preschool children with 36 to 42 months old. The questionnaire Affordances in the home Environment For Motor Development- AHEMD -18-42 Months and the test of gross motor development 2° Edition (TGMD-2) were used. The results showed one significant deficiency in the promotion of opportunities for the MD of children in the home environment, without negatively influencing their motor  development. It also demonstrates that these children’s maturational rhythm, and mainly the action of other Microsystems, can be supplying detected deficiencies in the home environment. Keywords: Affordances. Motor Skill. Preschool Children.